Analisis pembatalan faktur pajak - Dharmawan, Adrian Hartanto; Yuniarwati, Yuniarwati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to find out the factors causing the cancellation of Tax Invoices, the tax mechanism for canceling Tax Invoices after the issuance of e-Invoices, and the effect of canceling e-Invoices on companies. The research method used is descriptive qualitative, and the data source comes from primary and secondary data. Overall, using the E-Faktur application facilitates filling out and canceling tax invoices. However, the lack of dissemination of the procedures for using the E-Faktur application has caused many Taxable Entrepreneurs do not understand the procedures for filling out E-Invoices. The results showed that the factors causing the cancellation of tax invoices were transaction cancellations and filling errors. The tax mechanism for canceling output tax invoices uses the help of the E-Faktur application. Cancellation of tax invoices does not only affect the seller's PKP but also the buyer's PKP.